Newly employed nurses' transition into their new role in the ambulance service- a qualitative study - Klara Jepsen; Veronica Lindström; Jonas Wihlborg; Anna HÖrberg (BMC, 2024)
Abstract Background Nurses are essential to ensure safe and high-quality care worldwide. The World Health Organization (WHO) forecasts a shortfall of 5.9 million nurses by the year 2030, and in the ambulance service, the turnover rate ranges between 20% and 30%. With this study, we seek to increase knowledge by exploring the transition of newly employed experienced nurses into their roles in the ambulance service using the Meleis theory of transition. Through understanding transition, support for newly employed nurses can be developed, turnover rates can decrease, and in the long term, patient safety may increase. Design The study employed a qualitative approach. Methods Eighteen newly employed experienced nurses were individually interviewed four times during their first six months of employment. Deductive qualitative content analysis was used to analyse the data. The reporting of this research adheres to the COREQ checklist. Results The results show that the transition process for newly employed nurses in the ambulance service encompassed all five aspects of Meleis' transition theory: Awareness, Engagement, Change and Difference, Time Span, and Critical Points. The transition period varied among the participants, and it was also observed that not all nurses went through a transition in line with Meleis' theory. Additionally, there were findings that nurses highlighted the impact of the ambulance service culture on their transition. Conclusions The findings provide a more profound insight into how newly employed nurses with previous experience as nurses navigate their roles and transition into a new profession in a new context. An ambulance service where the organisation is aware of the newly employed nurses' transition processes and what the transition entails can develop and promote a supportive and permissive culture within the ambulance service. For newly employed nurses who are adequately supported, health transitions are more likely to occur, which may increase retention and in the long term increase patient safety. The insights gained from the study can empower ambulance organisations to improve their introduction programmes and offer enhanced support for newly employed experienced nurses entering the ambulance service.